Fly ash-based adsorption material and preparation method and application thereof
Patent Information
- Application Number
- CN202611477467.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]为解决现有技术中存在的技术问题,本发明提供一种粉煤灰基吸附材料及其制备方法和应用,以工业固废粉煤灰为基体,通过碱洗-酸浸结合聚吡咯改性粉煤灰的方式,获得制备工艺简洁、制备成本低廉、高比表面积且吸附性能好的粉煤灰基溴吸附材料;同时,所述粉煤灰基吸附材料能够与电化学氧化工艺有效协同,实现水环境中溴的高效提取,从根本上避免传统吸附法存在的设备腐蚀、氯代有机物污染问题,为工业固废粉煤灰的资源化利用和低成本提溴提供一种新方向
(1)本发明的粉煤灰基吸附材料,以粉煤灰作为基体,利用碱洗-酸浸结合聚吡咯负载的方式对粉煤灰进行改性,碱洗-酸浸可以溶去粉煤灰中存在的可溶性盐和杂质,使得粉煤灰获得更大的比表面积和孔隙率,极大提升了粉煤灰的吸附性能;以原位聚合的方式将聚吡咯负载于碱洗-酸浸粉煤灰上,有效避免了聚吡咯的堆积、团聚,使聚吡咯能够与溶液中溴单质充分接触,大幅度提升聚吡咯吸附点位的利用率。
Smart Images

Figure CN122974288A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of bromine adsorption materials technology, and in particular to a fly ash-based adsorption material, its preparation method, and its application. Background Technology
[0002] Fly ash refers to the fine ash collected from the flue gas after coal combustion by a dust collector. It mainly originates from the power and heat production industries and is one of the main solid wastes discharged from coal-fired power plants. Fly ash particles are mostly spherical with smooth surfaces; some are solid, and some are hollow. They have high adsorption activity and resemble cement in appearance, ranging in color from milky white to grayish-black, with darker colors generally indicating higher carbon content. With the development of the power industry, the amount of fly ash emitted by coal-fired power plants has increased year by year, and it has now become one of the largest industrial wastes. Currently, the resource utilization of fly ash mainly focuses on cement, concrete, and building material production, all of which are low-value-added uses with limited comprehensive utilization value. However, fly ash raw materials have a good adsorption basis, thus fly ash has the potential to develop low-cost adsorbents. However, the adsorption potential of untreated fly ash has not been fully activated, limiting its adsorption effect. Developing low-cost adsorbents to replace expensive adsorbents has become a research hotspot.
[0003] Bromine, the only non-metallic element that exists in liquid form at room temperature, is chemically highly reactive and possesses strong oxidizing properties. It can react with various substances to form a variety of inorganic and organic bromides, making it a crucial raw material for industrial processing. Bromine resources are mainly distributed in brine systems such as seawater, salt lake brines, and mine brine. Seawater is the resource type with the highest bromine content; reports indicate that the total bromine resources in seawater reach 100 trillion tons, accounting for 99% of the world's total bromine resources, earning it the title of "ocean element." This demonstrates the considerable recovery value of bromine resources in seawater.
[0004] Currently, the main bromine extraction processes include air blowing, ion exchange resin method, membrane separation method, and steam distillation method. Among these, air blowing is the most widely used and mature method for bromine extraction from seawater brine, but it also has problems such as poor raw material adaptability, high energy consumption, and limited automation. Adsorption methods have received widespread attention due to their simple operation and wide applicability. Adsorption bromine extraction refers to the method of using a porous adsorbent to adsorb ions from the aquatic environment onto the surface of the adsorbent. Commonly used adsorbents in adsorption methods include silver-based adsorbents and double metal hydroxides (LDHs). Adsorption methods first require acidification and oxidation of the raw material solution before using a bromine adsorbent to adsorb bromide ions. However, adsorption bromine extraction requires the use of chlorine gas for acidification and oxidation of the raw material solution, which not only corrodes equipment and increases maintenance costs but also produces chlorinated organic compounds, causing environmental pollution. Furthermore, the adsorbents used are relatively expensive. Electro-oxidation methods, by controlling the oxidation potential, avoid the presence of Cl in seawater... -Oxidation simultaneously achieves Br - The selective oxidation enrichment method is highly selective, environmentally friendly, and energy-efficient, and has great potential to replace the traditional bromine extraction oxidation process. Based on this, if a low-cost bromine adsorption material is developed, which can be combined with the selective oxidation effect of electro-oxidation, not only can the acidification process required by the traditional adsorption method be avoided, but the cost of bromine extraction can also be greatly reduced.
[0005] Chinese invention patent document CN121372371A discloses a method for preparing a highly selective bromide ion adsorbent. This method uses zirconium salt as a matrix, first reacting it with 2,5-dihydroxyterephthalic acid to prepare a zirconium-based MOF precursor, then modifying it with a thiol-modifying reagent to obtain a thiol-functionalized adsorbent. Finally, it uses protonation and titanate coupling agent doping to produce the bromide ion selective adsorbent. However, this method requires the use of multiple organic reagents (such as 2,5-dihydroxyterephthalic acid, N,N-dimethylformamide, titanate coupling agents, etc.) and hydrochlorides (such as mercaptoethylamine hydrochloride, EDCl, etc.) in the modification reaction; it also requires a complex four-step preparation process, which is difficult to operate. Furthermore, using zirconium salt as a matrix results in higher adsorbent costs compared to industrial waste fly ash matrices, which is not conducive to large-scale industrial production and application. Summary of the Invention
[0006] To address the technical problems existing in the prior art, this invention provides a fly ash-based adsorbent material, its preparation method, and its application. Using industrial solid waste fly ash as a matrix, a fly ash-based bromine adsorbent material with a simple preparation process, low preparation cost, high specific surface area, and good adsorption performance is obtained through an alkaline washing-acid leaching combined with polypyrrole-modified fly ash. Simultaneously, the fly ash-based adsorbent material can effectively synergize with electrochemical oxidation processes to achieve efficient bromine extraction from the aquatic environment, fundamentally avoiding the equipment corrosion and chlorinated organic pollution problems associated with traditional adsorption methods. This provides a new direction for the resource utilization and low-cost bromine extraction of industrial solid waste fly ash.
[0007] To solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a fly ash-based adsorbent material includes the following steps: Step S01: Screen the fly ash using a 100-200 mesh sieve, add the screened fly ash to a NaOH solution, heat to 50-70℃, keep warm and wash with alkali, separate and collect the solids, dry, and obtain alkali-washed fly ash. Step S02: Mix hydrochloric acid with alkaline-washed fly ash, stir at room temperature, separate and collect the solids, and dry them to obtain alkaline-washed and acid-leached fly ash. Step S03: Add the alkaline-washed and acid-leached fly ash and pyrrole to deionized water, disperse them evenly, add the polymerization initiator, control the reaction temperature at 3-5℃, keep the reaction at the temperature, separate and collect the solids, dry them, and obtain the fly ash-based adsorbent material.
[0008] Preferably, in step S01, the concentration of the NaOH solution is 1-3 mol / L; The mass-to-volume ratio of the screened fly ash to NaOH solution was 1 g: 5-15 mL.
[0009] Preferably, in step S01, the time for heat preservation and alkaline washing is 1-3 hours.
[0010] Preferably, in step S02, the concentration of hydrochloric acid is 15-30 wt%. The mass-to-volume ratio of alkaline-washed fly ash to hydrochloric acid is 1g:3-7mL.
[0011] Preferably, in step S02, the stirring time at room temperature is 4-6 hours.
[0012] Preferably, in step S03, the mass ratio of alkaline washing-acid leaching of fly ash, pyrrole, and deionized water is 1:0.41-1.23:50-70.
[0013] Preferably, in step S03, the polymerization initiator is one of the following: FeCl3·6H2O, ammonium persulfate, or potassium persulfate; The molar ratio of pyrrole to polymerization initiator is 1:2-4.
[0014] Preferably, in step S03, the heat preservation reaction time is 10-15 hours.
[0015] A fly ash-based adsorbent material prepared by the aforementioned method comprises: alkaline-washed and acid-leached fly ash, and a polypyrrole layer loaded on the alkaline-washed and acid-leached fly ash. The mass ratio of alkaline-acid-leached fly ash to polypyrrole layer is 1:0.41-1.23.
[0016] An application of the aforementioned fly ash-based adsorbent material in bromine-containing solutions for bromine extraction involves adding the fly ash-based adsorbent material to the bromine-containing solution, dispersing it evenly, and then controlling the oxidation potential at 1-1.5V to perform electro-oxidation treatment to remove Br from the bromine-containing solution. - It is oxidized to Br2, and at the same time, the fly ash-based adsorbent material adsorbs Br2.
[0017] Preferably, the mass-to-volume ratio of fly ash-based adsorbent material to bromine-containing solution is 1-3 mg: 1 mL.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The fly ash-based adsorbent material of the present invention uses fly ash as a matrix and modifies the fly ash by means of alkaline washing-acid leaching combined with polypyrrole loading. Alkaline washing-acid leaching can dissolve the soluble salts and impurities present in the fly ash, so that the fly ash can obtain a larger specific surface area and porosity, which greatly improves the adsorption performance of the fly ash. By loading polypyrrole onto alkaline-washed and acid-leached fly ash by in-situ polymerization, the accumulation and agglomeration of polypyrrole are effectively avoided, so that polypyrrole can fully contact with the bromine in the solution, which greatly improves the utilization rate of the polypyrrole adsorption sites.
[0019] (2) In the preparation of the fly ash-based adsorbent material of the present invention, the fly ash is pretreated by alkaline washing and acid leaching. Alkaline washing can not only dissolve the dense glassy body on the surface and promote the hydrolysis of silicon and aluminum components in the fly ash to generate more active sites, but also dissolve and wash away soluble salts to reduce interference with the adsorption process. Acid leaching can remove metal oxides and impurities that are easily soluble in acid, and further optimize the pore structure and composition of the fly ash. After alkaline washing and acid leaching, the specific surface area and porosity of the fly ash are significantly increased, which not only provides a basis for the efficient physical adsorption of bromine by fly ash, but also provides a larger adhesion area for subsequent polypyrrole loading modification.
[0020] Furthermore, this invention employs a method of loading polypyrrole onto alkaline-washed and acid-leached fly ash, which can fully utilize the abundant pores of the alkaline-washed and acid-leached fly ash as a framework, solving the problem of easy accumulation and agglomeration of polypyrrole, allowing the adsorption sites of polypyrrole to be fully exposed, and effectively improving the chemical complexation adsorption performance of polypyrrole for elemental bromine in solution.
[0021] (3) The fly ash-based adsorbent material of the present invention utilizes the physical enrichment of porous alkaline-washed and acid-leached fly ash in conjunction with the chemical adsorption of polypyrrole to achieve efficient adsorption of bromine in bromine-containing solutions. First, alkaline-washed and acid-leached fly ash with a porous structure is used as a substrate. Its large specific surface area and high porosity can physically adsorb and enrich bromine in bromine-containing solutions, thereby increasing the concentration of bromine in the fly ash pores. As a result, the polypyrrole loaded on alkaline-washed and acid-leached fly ash can come into contact with high concentrations of bromine, which greatly promotes the chemical adsorption of polypyrrole.
[0022] (4) The method for preparing the fly ash-based adsorbent material of the present invention successfully prepared a fly ash-based adsorbent material with high adsorption performance by combining alkaline washing-acid leaching with polypyrrole modification. The preparation process is simple, the reaction conditions are mild, the preparation cost is low, and the preparation process is green and environmentally friendly. Furthermore, the fly ash-based adsorbent material prepared by the method exhibits synergistic selective oxidation of Br by electro-oxidation. - Its function is to not only avoid the interference of traditional acidification processes and other ions, but also to realize the high-value and harmless utilization of solid waste, which has broad prospects for industrial application.
[0023] (5) The fly ash-based adsorbent material prepared in this invention exhibits excellent adsorption performance under synergistic electro-oxidation conditions. In an experiment, at a temperature of 25°C and an oxidation voltage of 1.25V, the adsorbent material was used to test a bromine-containing solution with a concentration of 330.35mg / L. After a 120-minute oxidation-adsorption experiment, the adsorbent adsorption capacity reached 74.79-126.68mg / g, of which the adsorption capacity of the 0.62PPy / MFA adsorbent material reached 126.68mg / g, which is 4.7 times and 2.2 times that of MFA and PPy, respectively. Analysis showed that this was because PPy was loaded on the MFA framework, which solved the problem of easy accumulation and aggregation of PPy, allowing PPy to expose more adsorption active sites. At the same time, the physical adsorption enrichment effect of MFA also promoted the adsorption of PPy, thereby effectively improving the adsorption performance of the adsorbent material. Attached Figure Description
[0024] Figure 1 SEM images of the adsorbent material prepared in Comparative Example 1; in the figure, (a) is the morphology of the screened fly ash; (b) is the morphology of the fly ash after alkali washing and acid leaching.
[0025] Figure 2 The images show the XRD patterns of the adsorbent materials prepared in Example 2 and Comparative Example 1.
[0026] Figure 3 The image shows the BET plot of the adsorbent material prepared in Example 2.
[0027] Figure 4 This is a theoretical analysis diagram of the selective oxidation of the carbon plate electrode in Experiment Example 4.
[0028] Figure 5 The graph shows the adsorption performance of the adsorbent material prepared in Example 2 at different potentials. Detailed Implementation
[0029] To provide a clearer understanding of the technical features, objectives, and effects of this invention, specific embodiments are now described. It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0030] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments of the present invention. As used herein, "first," "second," etc., are used to distinguish similar objects and are not used to describe a particular order or sequence. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0031] In a first aspect, embodiments of the present invention provide a method for preparing a fly ash-based adsorbent material, comprising the following steps: Step S01: Use a 100-200 mesh sieve to screen the fly ash, add the screened fly ash to NaOH solution, heat to 50-70℃, keep warm and wash with alkali, separate and collect the solids, dry, and obtain alkali-washed fly ash. Step S02: Mix hydrochloric acid with alkaline-washed fly ash, stir at room temperature, separate and collect the solids, and dry them to obtain alkaline-washed and acid-leached fly ash. Step S03: Add the alkaline-washed and acid-leached fly ash and pyrrole to deionized water, disperse them evenly, add the polymerization initiator (i.e., the oxidant that initiates polymerization), control the reaction temperature at 3-5℃, keep the reaction at the temperature, separate and collect the solids, dry them, and obtain the fly ash-based adsorbent material.
[0032] In this embodiment of the invention, fly ash is used as the matrix, and the fly ash is modified by a combination of alkali washing-acid leaching and polypyrrole loading. Alkali washing-acid leaching can dissolve soluble salts and impurities in fly ash, and give fly ash a larger specific surface area and porosity, effectively improving the adsorption performance of fly ash. Then, polypyrrole is loaded onto the alkali-washed and acid-leached fly ash by in-situ polymerization, which effectively avoids the accumulation and agglomeration of polypyrrole, and allows polypyrrole to fully contact with elemental bromine in bromine-containing solution, greatly improving the utilization rate of polypyrrole adsorption sites.
[0033] Preferably, in step S01, the concentration of the NaOH solution is 1-3 mol / L; the mass-to-volume ratio of the screened fly ash to the NaOH solution is 1 g: 5-15 mL.
[0034] Preferably, in step S01, the time for heat preservation and alkaline washing is 1-3 hours.
[0035] Preferably, in step S02, the concentration of hydrochloric acid is 15-30 wt%; the mass-to-volume ratio of alkaline-washed fly ash to hydrochloric acid is 1 g: 3-7 mL.
[0036] Preferably, in step S02, the stirring time at room temperature is 4-6 hours.
[0037] Preferably, in step S03, the mass ratio of alkaline washing-acid leaching of fly ash, pyrrole, and deionized water is 1:0.41-1.23:50-70.
[0038] Preferably, in step S03, the polymerization initiator is one of the following: FeCl3·6H2O, ammonium persulfate, potassium persulfate; the molar ratio of pyrrole to polymerization initiator is 1:2-4.
[0039] Preferably, in step S03, the heat preservation reaction time is 10-15 hours.
[0040] Secondly, embodiments of the present invention also provide a fly ash-based adsorbent material prepared by the aforementioned method, comprising: alkaline-washed and acid-leached fly ash, and a polypyrrole (PPy) layer loaded on the alkaline-washed and acid-leached fly ash.
[0041] Preferably, in the fly ash-based adsorbent material, the mass ratio of alkali-washed-acid-leached fly ash to polypyrrole layer is 1:0.41-1.23; more preferably, the mass ratio of alkali-washed-acid-leached fly ash to polypyrrole layer is 1:0.62.
[0042] In this embodiment of the invention, the fly ash-based adsorbent material utilizes the physical enrichment of porous alkaline-washed and acid-leached fly ash in conjunction with the chemisorption of polypyrrole to achieve efficient adsorption of bromine in bromine-containing solutions. Firstly, alkaline-washed and acid-leached fly ash with a porous structure is used as a substrate. Its large specific surface area and high porosity allow for the physical adsorption and enrichment of bromine in bromine-containing solutions, increasing the concentration of bromine within the fly ash pores. Consequently, the polypyrrole loaded on the alkaline-washed and acid-leached fly ash can come into contact with the high concentration of bromine, greatly promoting the chemisorption of polypyrrole.
[0043] Thirdly, embodiments of the present invention also provide the application of the aforementioned fly ash-based adsorbent material in bromine extraction from bromine-containing solutions. The fly ash-based adsorbent material is added to the bromine-containing solution, dispersed evenly, and then subjected to electro-oxidation treatment with an oxidation potential controlled at 1-1.5V to remove Br from the bromine-containing solution. - It is oxidized to Br2, and at the same time, the fly ash-based adsorbent material adsorbs Br2.
[0044] Preferably, the mass-to-volume ratio of fly ash-based adsorbent material to bromine-containing solution is 1-3 mg: 1 mL.
[0045] In this embodiment of the invention, the fly ash-based adsorption material can effectively synergize with the electrochemical oxidation process to achieve efficient extraction of bromine from the aquatic environment, fundamentally avoiding the equipment corrosion and chlorinated organic pollution problems existing in traditional adsorption methods for bromine extraction, and providing a new direction for the resource utilization and low-cost bromine extraction of industrial solid waste fly ash.
[0046] To enable those skilled in the art to more clearly understand the technical solution of the present invention, the present invention will be further described below with reference to some specific embodiments. The values in the samples prepared in each embodiment and comparative example represent the content of the substance. For example, 0.62PPy / MFA means that the mass ratio of polypyrrole to alkali-washed-acid-leached fly ash is 0.62:1, and so on.
[0047] Example 1 This embodiment provides a method for preparing a fly ash-based adsorbent material, specifically including the following steps: (1) Use a 100-mesh square hole sieve to screen fly ash. Add 10g of screened fly ash to 150mL of 1mol / L NaOH solution. Heat and stir at 70℃ for 3h. Collect the solid by vacuum filtration and dry to obtain alkaline washed fly ash. (2) Add 70 mL of 30 wt% hydrochloric acid to 10 g of alkaline-washed fly ash, stir continuously at room temperature for 6 h, centrifuge to collect the solid matter, dry it, and obtain alkaline-washed-acid-leached fly ash; (3) Add 1.0g of alkaline-washed and acid-leached fly ash and 0.41g (6.11mmol) of pyrrole to 50mL of deionized water, sonicate for 10min, then add 18.36mmol of FeCl3·6H2O, react for 10h under ice bath conditions at 3℃, centrifuge to collect the solid, dry, and obtain 0.41PPy / alkaline-washed and acid-leached fly ash adsorbent material, denoted as 0.41PPy / MFA.
[0048] This embodiment also provides a fly ash-based adsorbent material prepared by the aforementioned method, comprising: alkaline-washed and acid-leached fly ash, and a polypyrrole layer loaded on the alkaline-washed and acid-leached fly ash; the mass ratio of alkaline-washed and acid-leached fly ash to polypyrrole layer is 1:0.41.
[0049] Example 2 This embodiment provides a method for preparing a fly ash-based adsorbent material, specifically including the following steps: (1) Use a 200-mesh square hole sieve to screen fly ash. Add 10g of screened fly ash to 100mL of 3mol / L NaOH solution. Heat and stir at 70℃ for 3h. Collect the solid by vacuum filtration and dry to obtain alkaline washed fly ash. (2) Add 40 mL of 25 wt% hydrochloric acid to 10 g of alkaline-washed fly ash, stir continuously at room temperature for 5 h, centrifuge to collect the solid matter, dry it, and obtain alkaline-washed-acid-leached fly ash. (3) 1.0 g of alkaline-washed and acid-leached fly ash and 0.62 g (9.24 mmol) of pyrrole were added to 60 mL of deionized water and ultrasonically dispersed for 30 min. Then, 36.90 mmol of FeCl3·6H2O was added. After reacting for 15 h under ice bath conditions at 4 °C, the solid was collected by centrifugation and dried to obtain 0.62 PPy / alkaline-washed and acid-leached fly ash adsorbent material, which was denoted as 0.62 PPy / MFA.
[0050] This embodiment also provides a fly ash-based adsorbent material prepared by the aforementioned method, comprising: alkaline-washed and acid-leached fly ash, and a polypyrrole layer loaded on the alkaline-washed and acid-leached fly ash; the mass ratio of alkaline-washed and acid-leached fly ash to polypyrrole layer is 1:0.62.
[0051] Example 3 This embodiment provides a method for preparing a fly ash-based adsorbent material, specifically including the following steps: (1) Use a 100-mesh square hole sieve to screen the fly ash. Add 10g of the screened fly ash to 150mL of 2mol / L NaOH solution. Heat and stir at 50℃ for 3h. Collect the solid by vacuum filtration and dry to obtain alkaline washed fly ash. (2) Add 50 mL of 20 wt% hydrochloric acid to 10 g of alkaline-washed fly ash, stir continuously at room temperature for 4 h, centrifuge to collect the solid matter, dry it, and obtain alkaline-washed-acid-leached fly ash. (3) 1.0 g of alkaline-washed and acid-leached fly ash and 0.82 g (12.22 mmol) of pyrrole were added to 65 mL of deionized water and ultrasonically dispersed for 20 min. Then, 24.48 mmol of FeCl3·6H2O was added and reacted for 12 h under ice bath conditions at 5 °C. Afterward, the solid was collected by centrifugation and dried to obtain 0.82 PPy / alkaline-washed and acid-leached fly ash adsorbent material, which was denoted as 0.82 PPy / MFA.
[0052] This embodiment also provides a fly ash-based adsorbent material prepared by the aforementioned method, comprising: alkaline-washed and acid-leached fly ash, and a polypyrrole layer loaded on the alkaline-washed and acid-leached fly ash; the mass ratio of alkaline-washed and acid-leached fly ash to polypyrrole layer is 1:0.82.
[0053] Example 4 This embodiment provides a method for preparing a fly ash-based adsorbent material, specifically including the following steps: (1) Use a 200-mesh square hole sieve to screen fly ash. Add 10g of screened fly ash to 50mL of 3mol / L NaOH solution. Heat and stir at 60℃ for 1h. Collect the solid by vacuum filtration and dry to obtain alkaline washed fly ash. (2) Add 30 mL of 15 wt% hydrochloric acid to 10 g of alkaline-washed fly ash, stir continuously at room temperature for 5 h, centrifuge to collect the solid matter, dry it, and obtain alkaline-washed-acid-leached fly ash. (3) 1.0 g of alkaline-washed and acid-leached fly ash and 1.03 g (15.35 mmol) of pyrrole were uniformly added to 65 mL of deionized water, ultrasonically dispersed for 15 min, and then 46.12 mmol of FeCl3·6H2O was added. After reacting for 13 h under ice bath conditions at 5 °C, the solid was collected by centrifugation and dried to obtain 1.03 PPy / alkaline-washed and acid-leached fly ash adsorbent material, which was denoted as 1.03 PPy / MFA.
[0054] This embodiment also provides a fly ash-based adsorbent material prepared by the aforementioned method, comprising: alkaline-washed and acid-leached fly ash, and a polypyrrole layer loaded on the alkaline-washed and acid-leached fly ash; the mass ratio of alkaline-washed and acid-leached fly ash to polypyrrole layer is 1:1.03.
[0055] Example 5 This embodiment provides a method for preparing a fly ash-based adsorbent material, specifically including the following steps: (1) Use a 200-mesh square hole sieve to screen fly ash. Add 10g of screened fly ash to 100mL of 1mol / L NaOH solution. Heat and stir at 60℃ for 1h. Collect the solid by vacuum filtration and dry to obtain alkaline washed fly ash. (2) Add 60 mL of 25 wt% hydrochloric acid to 10 g of alkaline-washed fly ash, stir continuously at room temperature for 6 h, centrifuge to collect the solid matter, dry it, and obtain alkaline-washed-acid-leached fly ash; (3) 1.0 g of alkaline-washed and acid-leached fly ash and 1.23 g (18.33 mmol) of pyrrole were added to 70 mL of deionized water and ultrasonically dispersed for 25 min. Then, 36.72 mmol of FeCl3·6H2O was added. After reacting for 14 h under ice bath conditions at 3 °C, the solid was collected by centrifugation and dried to obtain 1.23 PPy / alkaline-washed and acid-leached fly ash adsorbent material, which was denoted as 1.23 PPy / MFA.
[0056] This embodiment also provides a fly ash-based adsorbent material prepared by the aforementioned method, comprising: alkaline-washed and acid-leached fly ash, and a polypyrrole layer loaded on the alkaline-washed and acid-leached fly ash; the mass ratio of alkaline-washed and acid-leached fly ash to polypyrrole layer is 1:1.23.
[0057] Comparative Example 1 Comparative Example 1 adopts the technical solution of Example 2, except that step (3) is omitted; other steps and process parameters are the same as in Example 2. The specific steps are as follows: (1) Use a 200-mesh square hole sieve to screen fly ash. Add 10g of screened fly ash to 100mL of 3mol / L NaOH solution. Heat and stir at 70℃ for 3h. Collect the solid by vacuum filtration and dry to obtain alkaline washed fly ash. (2) Add 40 mL of 25 wt% hydrochloric acid to 10 g of alkaline-washed fly ash, stir continuously at room temperature for 5 h, centrifuge to separate and collect the solids, dry them, and obtain alkaline-washed-acid-leached fly ash, denoted as MFA.
[0058] Comparative Example 2 Comparative Example 1 adopts the technical solution of Example 2, except that steps (1) and (2) are omitted; and the addition of alkaline washing-acid leaching fly ash is omitted in step (3). Other steps and process parameters are the same as in Example 2. The specific steps are as follows: 0.62 g (9.24 mmol) of pyrrole was added to 60 mL of deionized water and ultrasonically dispersed for 30 min. Then, 36.90 mmol of FeCl3·6H2O was added, and the mixture was reacted in an ice bath at 4 °C for 15 h. The solid was collected by centrifugation, dried, and polypyrrole was obtained, denoted as PPy.
[0059] Experimental Example 1 Scanning electron microscopy was used to characterize the fly ash and alkali-washed-acid-leached fly ash MFA from Comparative Example 1 after screening through a 200-mesh square-hole sieve. The results are as follows: Figure 1 As shown. Figure 1 In the image, (a) shows the morphology of the sieved fly ash. It can be seen that the fly ash sieved through a 100-mesh square hole sieve is composed of spherical structures with a diameter of 2-5 μm and its surface is obviously smooth. (b) shows the morphology of fly ash after alkali washing and acid leaching. It can be seen that after alkali washing and acid leaching, the surface of the screened fly ash becomes significantly rougher, the smooth surface is destroyed, and a large number of pores are generated. This indicates that the alkali washing combined with acid leaching removes unstable substances such as metals and salts that are soluble in acids and alkalis from the fly ash, providing a relatively stable support framework for the subsequent preparation of PPy / MFA composite adsorbent materials. At the same time, the large number of pores generated can not only greatly increase the specific surface area of the adsorbent and provide more attachment sites for the loading of polypyrrole, but also facilitate the uniform distribution of polypyrrole and effectively solve the problem of polypyrrole agglomeration. In addition, the large number of pores generated will expose more adsorption sites, which is more conducive to the physical adsorption and enrichment of bromine by the fly ash itself. The high concentration of bromine will further promote the chemical complexation adsorption of polypyrrole, thereby greatly improving the adsorption capacity of the loaded adsorbent material for bromine.
[0060] Experimental Example 2 The adsorbent materials prepared in Example 2 and Comparative Example 1 were characterized by XRD, and the results are as follows: Figure 2As shown in the figure, MFA exhibits similarities to mullite (Al) at 2θ=16.4°, 2θ=26.01°, 2θ=26.29°, 2θ=30.98°, 2θ=33.25°, 2θ=35.28°, 2θ=39.28°, and 2θ=40.88°. 2.3 Si 0.7 O 4.85 The diffraction peaks of the standard card PDF#74-2419 of fly ash are consistent with those of quartz (SiO2), and the corresponding crystal planes are (110), (200), (120), (001), (220), (111), (201), and (121). The diffraction peaks at 2θ=20.8° and 2θ=26.6° are consistent with those of the standard card PDF#99-0088 of quartz (SiO2), and the corresponding crystal planes are (100) and (011). The characteristic peaks of the modified 0.62PPy / MFA did not shift, which shows that PPy only adheres to the surface of MFA and does not affect the original crystal structure of the MFA skeleton. At the same time, it also shows that the modification of Example 2 (i.e., loading PPy) can ensure the chemical stability of the fly ash skeleton.
[0061] Experimental Example 3 BET tests were performed on the samples from Example 2 and the fly ash samples (i.e., the fly ash screened in Example 2), and the test results are shown in the table below. Figure 3 As shown in the figure, the slopes of the fly ash sample and the 0.62 PPy / MFA BET adsorption test are 0.749 and 0.41, respectively, and the specific surface areas are 5.67 m², respectively. 2 / g and 10.44m 2 The / g indicates that the alkaline washing-acid leaching treatment effectively expanded the specific surface area of fly ash, with pore sizes ranging from 0-2.384 nm and 0-2.360 nm, respectively. The pore size of 0.62 PPy / MFA is slightly lower than that of fly ash, which is due to the PPy loading on the surface and inside the pores of the fly ash, affecting its pore size. Specific BET test data are shown in the table below.
[0062]
[0063] Test Example 4 To verify the selective oxidation of Br by the electrode - To assess the feasibility of the technique, linear sweep voltammetry was performed on a 0.067 mol / L phosphate buffer solution, as well as 1 mol / L NaBr, 1 mol / L NaCl, and 0.5 mol / L Na₂SO₄ solutions prepared from the phosphate buffer solution, to determine the optimal Br₂ concentration when using a carbon plate as the working electrode. - and Cl - The potentials during oxidation are shown. The experimental results are as follows: Figure 4 As shown.
[0064] pass Figure 4 It can be seen that before the voltage reaches 1.0V, the voltammetric characteristic curve of the NaBr solution remains near the current of 0mA, indicating that Br - Electro-oxidation had not yet occurred; when the potential reached 1.0V, its voltammetric characteristic curve showed an inflection point, and the electrolytic device began to produce current. At the same time, the solution began to turn yellow, and bubbles began to appear on the surface of the platinum electrode. This indicates that Br - Oxidation begins; once the potential exceeds 1.0V, the current increases linearly with increasing potential, the yellow color of the solution gradually deepens, and numerous bubbles are generated on the surface of the platinum electrode (counter electrode). Br - Electro-oxidation continues; therefore, when a carbon plate electrode is used as the working electrode, Br - The electro-oxidation begins at a potential of 1.0V; similar to Br. - The analytical method showed that when the potential was set at 1.5V, the linear scan of the NaCl solution exhibited the same experimental phenomenon, indicating that when the carbon plate electrode was used as the working electrode, Cl... - The electro-oxidation begins at an electrode potential of 1.5V; thus, this invention demonstrates that by selecting an oxidation potential between 1.0 and 1.5V, Br can be achieved. - Selective oxidation, while avoiding Cl. - Oxidation effectively prevents chlorine from interfering with the adsorption process of bromine.
[0065] Experimental Example 5 To verify the effect of different polypyrrole loading ratios on the bromine extraction performance of fly ash-based adsorbents, adsorption and bromine extraction tests were conducted on the adsorbents prepared in Examples 1-5 and Comparative Examples 1-2. Specifically, 0.1 g of each adsorbent was uniformly dispersed in 100 mL of a pre-prepared bromine-containing solution with a bromide ion concentration of 330.35 mg / L, and an electro-oxidation-adsorption experiment was performed at 25°C and 1.25 V. During this process, an oxidation voltage of 1.25 V was used to oxidize the Br₂ in the solution. - It is oxidized to Br2, and the adsorbent material dispersed in the bromine-containing solution adsorbs the Br2.
[0066] After continuous electro-oxidation-adsorption experiments for 120 min, 10 mL of the adsorbed solution was collected, and the concentration of bromide ions in the solution (i.e., the concentration of bromide ions after adsorption) was measured. The adsorption capacity of the adsorbent was then calculated; the adsorption capacity is the ratio of the mass of adsorbed Br2 (mg) to the mass of the adsorbent (g). The specific results are shown in the table below:
[0067] By comparing the concentration of bromide ions in the solutions after adsorption in Examples 1-5, it can be seen that the 0.62PPy / MFA adsorbent material prepared in Example 2 has the lowest concentration of bromide ions in the solution after adsorption, with an adsorption capacity of 126.68 mg / g. This indicates that the adsorption performance is best when the mass ratio of PPy to MFA is 0.62:1, representing the optimal loading ratio. It also shows that too much or too little PPy loading will affect the performance of the adsorbent material. Too little PPy loading results in a weaker chemical complexation reaction and lower co-adsorption efficiency with the MFA framework, leading to insufficient improvement in adsorbent performance. Conversely, too much PPy loading causes accumulation of PPy on the MFA surface, potentially clogging the pores of the MFA framework. This not only masks some of the active adsorption sites of PPy but also severely affects the bulk physical adsorption process of MFA, limiting the adsorbent's adsorption performance for elemental bromine.
[0068] Compared to Example 2, the concentration of bromide ions in the solution after MFA adsorption in Comparative Example 1 was 303.38 mg / L, and the adsorption capacity was only 26.97 mg / g. In contrast, the adsorption capacity of 0.62 PPy / MFA in Example 2 reached 126.68 mg / g, which is 4.7 times that of MFA in Comparative Example 1. This indicates that the chemical complexation adsorption reaction generated by PPy loading, in synergy with the physical adsorption of MFA, greatly improves the performance of the adsorbent material, and also demonstrates the importance of PPy loading for modifying MFA adsorbent materials.
[0069] Compared with Example 2, the concentration of bromide ions in the solution after PPy adsorption in Comparative Example 2 was 272.82 mg / L, and the adsorption capacity was 57.53 mg / g. The adsorption capacity of 0.62 PPy / MFA in Example 2 was 2.2 times that of PPy in Comparative Example 2. This is because an appropriate amount of PPy is loaded on the MFA framework. The high porosity and specific surface area of the MFA framework will make PPy uniformly dispersed on the surface of the MFA framework, avoiding the problem of easy accumulation and aggregation of PPy. This allows PPy to expose more adsorption active sites. At the same time, the physical adsorption enrichment effect of MFA will also promote the adsorption of PPy, thereby improving the adsorption performance of the adsorption material.
[0070] Experimental Example 6 Based on Experiment 5, to investigate the effect of different bromine oxidation potentials on the adsorption effect of the adsorbent material, 0.1 g of the 0.62 PPy / MFA adsorbent material from Example 2 was dispersed into seven pre-prepared 100 mL bromine-containing solutions with a bromide ion concentration of 330.35 mg / L at a temperature of 25 °C. The oxidation electrode potentials for the seven groups were set to 1.1 V, 1.15 V, 1.2 V, 1.25 V, 1.3 V, 1.35 V, and 1.4 V, respectively. After 120 min of oxidation-adsorption experiment, 10 mL of the adsorbed solution was taken for bromide ion concentration analysis; the specific results are as follows: Figure 5 As shown.
[0071] Depend on Figure 5 It can be seen that before 1.25V, as the electrode potential increases, the concentration of bromide ions in the solution decreases and the adsorption capacity increases, reaching a maximum of 126.68 mg / g at 1.25V. However, with further increases in electrode potential, the adsorption capacity slowly decreases. Analysis shows that this is mainly because the increased potential leads to enhanced adsorption of other anions on the electrode surface, occupying the bromide ion concentration. - The reaction site of Br - The oxidation reaction was hindered. Therefore, this indicates that the electro-oxidation-adsorption performance is optimal when the electrode potential is set at 1.25V, and also shows that a higher electrode potential is not entirely conducive to the bromine extraction reaction.
[0072] Unless otherwise stated, all percentages used in this invention are mass percentages.
[0073] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a fly ash-based adsorbent material, characterized in that, Includes the following steps: Step S01: Screen the fly ash using a 100-200 mesh sieve, add the screened fly ash to a NaOH solution, heat to 50-70℃, keep warm and wash with alkali, separate and collect the solids, dry, and obtain alkali-washed fly ash. Step S02: Mix hydrochloric acid with alkaline-washed fly ash, stir at room temperature, separate and collect the solids, and dry them to obtain alkaline-washed and acid-leached fly ash. Step S03: Add the alkaline-washed and acid-leached fly ash and pyrrole to deionized water, disperse them evenly, add the polymerization initiator, control the reaction temperature at 3-5℃, keep the reaction at the temperature, separate and collect the solids, dry them, and obtain the fly ash-based adsorbent material.
2. The method for preparing the fly ash-based adsorbent material according to claim 1, characterized in that, In step S01, the concentration of the NaOH solution is 1-3 mol / L; The mass-to-volume ratio of the screened fly ash to NaOH solution was 1 g: 5-15 mL.
3. The method for preparing the fly ash-based adsorbent material according to claim 1, characterized in that, In step S01, the time for heat preservation and alkaline washing is 1-3 hours.
4. The method for preparing the fly ash-based adsorbent material according to claim 1, characterized in that, In step S02, the concentration of hydrochloric acid is 15-30 wt%. The mass-to-volume ratio of alkaline-washed fly ash to hydrochloric acid is 1g:3-7mL.
5. The method for preparing the fly ash-based adsorbent material according to claim 1, characterized in that, In step S02, the stirring time at room temperature is 4-6 hours.
6. The method for preparing the fly ash-based adsorbent material according to claim 1, characterized in that, In step S03, the mass ratio of alkaline washing-acid leaching of fly ash, pyrrole, and deionized water is 1:0.41-1.23:50-70.
7. The method for preparing the fly ash-based adsorbent material according to claim 1, characterized in that, In step S03, the polymerization initiator is one of the following: FeCl3·6H2O, ammonium persulfate, or potassium persulfate; The molar ratio of pyrrole to polymerization initiator is 1:2-4.
8. The method for preparing the fly ash-based adsorbent material according to claim 1, characterized in that, In step S03, the heat preservation reaction time is 10-15 hours.
9. A fly ash-based adsorbent material prepared by the preparation method according to any one of claims 1-8, characterized in that, include: Alkali-washed and acid-leached fly ash, and a polypyrrole layer loaded on the alkali-washed and acid-leached fly ash; The mass ratio of alkaline-acid-leached fly ash to polypyrrole layer is 1:0.41-1.
23.
10. An application of the fly ash-based adsorbent material as described in claim 9 in bromine extraction from bromine-containing solutions, characterized in that, The fly ash-based adsorbent material was added to a bromine-containing solution and dispersed evenly. Then, the oxidation potential was controlled at 1-1.5V for electro-oxidation treatment to remove Br from the bromine-containing solution. - It is oxidized to Br2, and at the same time, the fly ash-based adsorbent material adsorbs Br2.
Citation Information
Patent Citations
Preparation method of high-selectivity bromide ion selective adsorbent
CN121372371A